Advertisement effectiveness and choice of fast food restaurant: an exploratory study of Malay Muslim consumers - Haque, Ahasanul; Sayyed Ahmad, Mohd. Ismail (s.n, 2012)
The purpose of this paper is to explore customer’s views on fast food restaurants advertising. Data were collected by using convenient sampling method from Klang Valley area, Malaysia. 350 questionnaires were distributed and recorded with a response rate of 85 per cent. The result of the research shows that Malay Muslim customers are more attracted by internet advertisement followed by commercial advertising; print advertisement; likeability towards advertisements; entertainments in advertisements, made less of a contribution. The findings suggested some significant of implications which will help advertisers to create better fast food restaurant advertisements. For example, managers can change their slogans based on current situations which will help them to prepare on create suitable advertising for customers.